Diagnostic accuracy of acute appendicitis by comparing clinical judgment of surgeons and Alvarado scoring in suspected acute appendicitis - Bhusal, Ishory; Agarwal, Chandra Shekhar; Gupta, Rakesh Kumar; Sah, Suresh Prasad (International Surgery Journal, 2021)
Background: The Alvarado score is a clinical scoring system used in the diagnosis of acute appendicitis. The aim of the study was to compare the clinical judgment of surgeons and Alvarado score in diagnosing acute appendicitis within Nepalese people and to refine the score and suggest a new score to make a more accurate diagnosis of acute appendicitis. Methods: In this prospective, parallel-group, quasi-randomized study of patients presenting at a tertiary hospital in eastern Nepal with suspected appendicitis during 1 year were assigned in weekly alternation to either group A or group B. The group A patients were treated on the basis of their Alvarado score, and the group B patients based on the clinical judgment. The correctness of the methods was assessed by the final histology. Results: In this study, the mean age of patients in Alvarado group was 26.45 years and in clinical judgment was 28.68 years. The sensitivity, the specificity, the diagnostic accuracy, the positive predictive value and negative appendectomies in Alvarado group were 95.5%, 68.9%, 90.91%, 93.4% and 6.56% respectively whereas in clinical judgment group were 98.51%, 85.71%,496.4%, 97.04% and 3.59% respectively. Conclusions: This study showed clinical judgment to be more reliable in the diagnosis of acute appendicitis than the Alvarado score, but the score is a useful diagnostic aid, especially for young colleagues. The use of the new scoring system has become easier. It includes fewer criteria as well as an important and sensitive predictor: the ultrasound investigation.